2021
DOI: 10.24002/biota.v6i3.4372
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Rhizoctonia Induction on Leaf Thickness of Orchids Infected by Odontoglossum ringspot virus (ORSV)

Abstract: Orchids have high economic value so that they are potential to be cultivated. The species most popular with people are Dendrobium and Phalaenopsis. However, there are major obstacles that can affect orchid growth, namely viral infections. The type of virus reported to infect the most is ORSV. This viral infection can inhibit plant growth, reduce flower quality and marketability. There are also symptoms of viral infection in the form of mosaic, chlorotic, streak, and necrosis. One of the efforts to overcome vir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
7
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…This was in accordance with the research of Mahfut 7 which states that the lignin in the orchid transporting bundle functions to protect the evaporation of water during the transportation of nutrients and photosynthesis products so that the lignin is thicker. In this context, the above statement was supported by the research of Arifannisa et al 9 which stated that the lignin contained in the xylem of tomato plantlets induced by salicylic acid showed a greater thickness than K.…”
Section: Discussionmentioning
confidence: 74%
See 4 more Smart Citations
“…This was in accordance with the research of Mahfut 7 which states that the lignin in the orchid transporting bundle functions to protect the evaporation of water during the transportation of nutrients and photosynthesis products so that the lignin is thicker. In this context, the above statement was supported by the research of Arifannisa et al 9 which stated that the lignin contained in the xylem of tomato plantlets induced by salicylic acid showed a greater thickness than K.…”
Section: Discussionmentioning
confidence: 74%
“…This assumption is reinforced by the research of Mahfut et al 11 that the results of the transverse incision of the roots of the Thrixspermum subulatum orchid showed that peloton was degraded in some cortical cells with peloton not completely filling the cortical cells. This assumption was reinforced by the results of research by Arifannisa et al 9 who found two types of peloton in the dendrobium root cortex, namely peloton that filled cortical cells completely and did not completely fill cortical cells. A peloton that does not completely fill cortical cells is declared a degraded peloton.…”
Section: Discussionmentioning
confidence: 87%
See 3 more Smart Citations